War of the century when Hitler fought Stalin - Rees, Laurence 1957-.; West, Samuel 1966-.; Warner Home Video (Firm).; BBC Video (Firm). (London BBC Worldwide Limited, 2004)
High hopes - Invade the Soviet Union? What a crazy idea! But to Hitler, it seemed like a good one at the time. The total annihilation of Russia would mean not only the death of Communism and the interior Slavs, but living space for the voracious Reich. But Hitler overlooked two things: the withering Soviet winters and the callous cruelty of Stalin's rearguard action. By the end of the war 30 million people had died, and while it could be said that Hitler lost, it was hardly a triumph for the Kremlin; Spiral of terror- During the battle of Moscow, Hitler forced his armies to stand their ground despite brutally cold conditions. To prevent his soldiers from leaving the front line, Stalin ordered special blocking detachments to shoot all deserters. Such brutality set the tone for the rest of the war. And it wasn't just the soldiers who suffered. The Soviet leadership instructed Soviet partisans operating in the countryside to kill anyone thought to be disloyal; Learning to win- In the spring of 1942, Hitler launched a two-pronged attack in what he believed would ne his last offensive in the East. One set of troops headed towards Baku, the other towards Stalingrad and the Volga. But after more than a year of bitter defeats, the exhausted and demoralized Soviet army changed tack. Soviet generals no longer instructed their soldiers to stand their ground at all costs instead they told them to simply avoid capture and continue fighting; Vengeance- The desire to conquer Russia has repeatedly proved the downfall of expansionist leaders yet, at the height of his power, Hitler thought he could succeed where Napoleon had failed. In 1941, he broke the golden rule of warfare never to fight on opposite fronts, and marched on Russia. It was the most catastrophic mistake of World War Two. While the West prefers to think that they won the Second World War, in reality the Western front was always a sideshow to the main event. Hitler's brutal invasion of the Soviet Union and Stalin's subsequent fight back was the bloodiest war in history- more than 30 million people lost their lives.
Disc 1. High hopes (47 min., 34 sec.) -- Spiral of terror / Ian Kershaw (48 min., 07 min.) -- Disc 2. Learning to win (48 min., 58 sec.) -- Vengeance (47 min., 50 sec.)
Summary taken from cover.
Narrator, Samuel West ; film editor, Alan Lygo.
With English subtitles
Keywords: Hitler, Adolf -- 1889-1945.; Stalin, Joseph -- 1879-1953.; World War, 1939-1945 -- Campaigns -- Eastern Front; Soviet Union -- History -- German occupation, 1941-1944.; Germany -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- Germany; Germany -- Foreign relations -- 1933-1945.; Soviet Union -- Foreign relations -- 1917-1945.; Documentary films